STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI LUAR JAM PELAJARAN SEBAGAI LABORATORIUM SOSIAL PENDIDIKAN AGAMA ISLAM MADRASAH IBTIDAIYAH BAITUL HIKMAH KEDIRI - Widyawati (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2022)
The purpose of this study was to determine the implementation and results of the Islamic religious education (PAI) learning strategy outside of class hours as a social laboratory and also to determine the process of monitoring and assessing religious education learning outside of class hours as a social laboratory at MI BAITUL HIKMAH KEDIRI. This research was conducted through data collection using observation, interview, and document recording techniques systematically. In addition, the research design was applied by making direct observations and recording systematically about the phenomena being investigated. Based on the results of the study, it can be concluded that learning Islamic religious education that is carried out outside of class hours is a religious activity in the context of actualizing religious education that is carried out in class hours. Learning Islamic religious education that is carried out outside of class hours such as dhuha prayer in congregation, dzuhur prayer in congregation, Friday prayer, tarawih prayer for a full month, training in reading the Koran for students who have difficulty or are unable to read the Koran properly. fluency, zakat fitrah, qurban and Islamic Holidays (PHBI) strongly support formal religious learning programs, so that students are able to apply Islamic religious education properly and correctly. Learning Islamic religious education outside of class hours uses a hidden curriculum approach, which is a curriculum that is implemented outside the structured curriculum in lessons or PBM in the classroom. Also uses active learning, where students carry out religious activities responsibly and actively and creatively. Supporting factors for learning religious education outside of class hours are relatively active students, school and parent support and adequate infrastructure. While the inhibiting factor faced by Islamic religious education teachers in carrying out Islamic religious education learning outside of class hours is that there is still a difference in the understanding of the importance of religious education compared to general lessons so that sometimes in its application in the field of religious lessons it is always secondary